2013
DOI: 10.5688/ajpe779198
|View full text |Cite
|
Sign up to set email alerts
|

A Workshop on Smoking Cessation for Pharmacy Students

Abstract: Objective. To develop, implement, and evaluate a targeted educational intervention focusing on smoking cessation with final-year undergraduate pharmacy students. Design. A smoking-cessation educational workshop entitled Smoking Cessation in Pharmacy (SCIP) was designed on the principles of adult learning and implemented with a full cohort of final-year undergraduate pharmacy students at the University of Sydney. A previously validated questionnaire testing the knowledge and attitudes of respondents was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
2
11
0
Order By: Relevance
“…Similar to the previous studies (Schmelz AN et al, 2010, Corelli KL et al, 2005, Saba M et al, 2013, the results of this pilot study was found that TEP had positive effect on students' knowledge, perceived role, self-efficacy, and ability to perform tobacco cessation counseling. These findings are notable because such program was entirely new in Indonesia.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to the previous studies (Schmelz AN et al, 2010, Corelli KL et al, 2005, Saba M et al, 2013, the results of this pilot study was found that TEP had positive effect on students' knowledge, perceived role, self-efficacy, and ability to perform tobacco cessation counseling. These findings are notable because such program was entirely new in Indonesia.…”
Section: Discussionsupporting
confidence: 77%
“…15,16 In our study, two-thirds of the third-year students were able to provide smoking cessation counseling appropriately following the module and role-play interventions, corroborating findings from other studies. [15][16][17] In this study, a major limitation was that we did not know if students accessed the CSCSP online module. The module was incorporated as optional reading material, and its content was not assessed as part of their final examination.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Studies utilizing active-learning strategies to provide students with knowledge and skills for smoking cessation counseling also reported positive outcomes. [15][16][17] However, none of these studies used modules developed for practicing health care professionals. In our study, the CSCSP module designed for practicing health care professionals was tested for its suitability to equip undergraduate pharmacy students with knowledge and skills at graduation to assist smokers with quitting.…”
mentioning
confidence: 99%
“…It may also be worthwhile to consider the mandatory inclusion of smoking cessation in the pharmacy school curriculum as suggested in the FGD. Targeted intervention workshops for pharmacy students have been shown to be effective and may also be considered 37 . Nicotine replacement therapies (NRTs) are commonly used over-thecounter treatments for smoking cessation 38,39 .…”
Section: Research Articlementioning
confidence: 99%